NLR family pyrin domain containing 3 (NLRP3) inflammasome gene polymorphism rs7512998 (C>T) predicts aging-related increase of blood pressure, the TAMRISK study. Issue 1 (December 2015) - Kunnas, Tarja; Määttä, Kirsi; Nikkari, Seppo
Abstract Background The activation of NLR family pyrin domain containing 3 (NLRP3) inflammasome by cellular stress leads to activation of the inflammasome, and NLRP3 gene polymorphisms have been associated with autoinflammatory diseases. Inflammasomes have also been implicated in the initiation or progression of metabolic disorders such as atherosclerosis, type 2 diabetes and obesity. The association of NLRP3 genetic variant rs7512998 with blood pressure and hypertension was studied in a 50-year-old Finnish cohort with a subpopulation who had available data on blood pressure measurements also at the age of 45 years. Results NLRP3 gene polymorphism rs7512998 C-allele was associated with higher systolic (p  = 0.006) and diastolic (p  = 0.011) blood pressure compared to the TT-genotype carriers in 50-year-old subjects. In addition, by analysis of variance for repeated measures between ages of 45- and 50 years there was a significant time by genotype interaction; blood pressure increased more in subjects with the C-allele both in systolic (p  = 0.035) and diastolic (p  = 0.012) values. However, no association with diagnosed hypertension was found. Conclusion We report for the first time that NLRP3 gene polymorphism rs7512998 was associated with systolic and diastolic blood pressure in 50-year-old subjects. In addition, an effect of this variation upon blood pressure was seen in these same subjects in a 5-year follow-up from a 45-year-old cohort to 50 years of age.